The effect of laser pulse bandwidth on the measurement of the frequency fluctuation correlation functions in 2D electronic spectroscopy - Nowakowski, Paweł J. (2020)
Several methods have been proposed to obtain the frequency fluctuation correlation function (FFCF) of a transition from the 2DES spectra without complicated fitting procedures. Although all were shown to give correct values in idealized conditions, this might not be applicable in real experimental circumstances. Here, we observe the effects of using different bandwidth excitation pulses in three commonly used methods: ellipticity, center line slope of slices along excitation (CLSω1) and detection (CLSω3) frequencies. The studies were performed on the Qy transition of chlorophyll a. We show that the CLSω3 method gives consistent results for all bandwidths used. For the other two methods, the recovered FFCF values decrease in magnitude with decreasing excitation pulse bandwidths. We also show that by applying the simplified expressions derived by Do et al., incorporating finite pulses in 2DES spectra simulation, we can recover accurate FFCFs using any of these methods.